A new species of the genus Achalinus (Squamata: Xenodermidae) from Son La Province, Vietnam - Ha, Nghia Van; Ziegler, Thomas; Sy, Tuong Dinh; Le, Minh Duc; Nguyen, Truong Quang; Luu, Vinh Quang (Zootaxa, 2022)
A new snake of the genus Achalinus Peters, 1869 is described based on an adult male specimen from Son La Province, Vietnam. Achalinus vanhoensis sp. nov. can be distinguished from its congeners by a combination of the following characters: 1) maxillary teeth 32; 2) suture between the internasals distinctly longer than that between the prefrontals; 3) loreal fused with prefrontal, prefrontals stretch towards the supralabials; 4) dorsal scales in 25–23–23 rows, keeled; 5) supralabials six (left) and seven (right); 6) infralabials six; 7) temporals 2+2, the two anterior temporals in broad contact with eye; 8) ventrals 176; 9) subcaudals 84, entire; 10) cloacal entire; 11) dorsum in preservative dark purple grey above; 12) venter somewhat lighter with yellow-edged scales in the chin region, including infralabials; 13) posterior edges of ventrals and subcaudals with yellow margin. In the molecular analysis, the new species is recovered as a sister taxon of Achalinus timi, a species endemic to Vietnam, and genetically the two species are around 5% divergent from each other based on a fragment of the mitochondrial COI gene. This discovery brings the number of Achalinus species known from Vietnam to nine.